2011
DOI: 10.1175/bams-d-10-05003.1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Characteristics of Climate in Medieval Times Revisited

Abstract: The increase in high-resolution proxy records over expanding areas of the globe helps deepen understanding of the unusual climate patterns-and the forcing mechanisms responsible for them-during the years 950 to 1400. C limate in medieval times, a period usually understood to extend from A.D. ~950 to ~1400, is of considerable interest to students of modern and future climate. This is because the period differs from recent centuries mainly by predating the Industrial Revolution with its associated changes in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
96
0
8

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(114 citation statements)
references
References 100 publications
10
96
0
8
Order By: Relevance
“…suggests increased biomass burning during the Medieval Climate Anomaly (MCA). The MCA is known to have been a warm and drought-prone period in many regions globally (27). In Alaska, lake sediment analyses suggest near-modern temperature during the MCA (28,29) accompanied by relatively arid conditions (29,30), perhaps analogous to the recent trend of diminishing water availability driven by increased evapotranspiration because of warming (31).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…suggests increased biomass burning during the Medieval Climate Anomaly (MCA). The MCA is known to have been a warm and drought-prone period in many regions globally (27). In Alaska, lake sediment analyses suggest near-modern temperature during the MCA (28,29) accompanied by relatively arid conditions (29,30), perhaps analogous to the recent trend of diminishing water availability driven by increased evapotranspiration because of warming (31).…”
Section: Resultsmentioning
confidence: 99%
“…Although the timing and magnitude of the MCA were spatially heterogeneous, temperatures during the period approached 20 th century values across much of the Northern Hemisphere, and many areas experienced exceptional hydroclimatic variability (27). Paleorecords of the period thus offer an opportunity to assess the ecosystem impacts of ongoing and future climate change (37).…”
Section: Pushing the Limits: Recent Fire Regime Dynamics And Implicatmentioning
confidence: 99%
See 1 more Smart Citation
“…The past 1500 years have been characterized by significant changes in the global climate (e.g., Jansen et al 2007;Jones et al 2009;Mann et al 2009;Diaz et al 2011;Graham et al 2011). The Northern Hemisphere (NH) experienced a relatively warm period known as the Medieval Climate Anomaly [MCA; ;950-1250 CE (Common Era)], during which the hemispheric-scale temperature was similar to twentieth-century levels.…”
Section: Introduction a The Climate Of The Past 1500 Yearsmentioning
confidence: 99%
“…The cause of the MCA is unclear, with climate models unable to reproduce the reconstructed warmth of this period (e.g., Mann et al 2009;Fern andez-Donado et al 2013). When combined with proxy evidence, this suggests that the MCA may have arisen from an internal reorganization of the climate system (Diaz et al 2011;Graham et al 2011). While detection and attribution studies have found a significant role of volcanic eruptions in driving the preindustrial Northern Hemisphere climate, the availability of proxy data has restricted these studies to the extratropics and/or periods shorter than 1000 years (Hegerl et al 2003(Hegerl et al , 2007a.…”
Section: Introduction a The Climate Of The Past 1500 Yearsmentioning
confidence: 99%